Use of mixed reality for improved spatial understanding of liver anatomy - Pelanis, Egidijus; Kumar, Rahul P.; Aghayan, Davit L.; Palomar, Rafael; Fretland, Åsmund A.; Brun, Henrik; Elle, Ole Jakob; Edwin, Bjørn (Minimally invasive therapy and allied technologies, 2020)
Introduction: In liver surgery, medical images from pre-operative computed tomography and magnetic resonance imaging are the basis for the decision-making process. These images are used in surgery planning and guidance, especially for parenchyma-sparing hepatectomies. Though medical images are commonly visualized in two dimensions (2D), surgeons need to mentally reconstruct this information in three dimensions (3D) for a spatial understanding of the anatomy. The aim of this work is to investigate whether the use of a 3D model visualized in mixed reality with Microsoft HoloLens increases the spatial understanding of the liver, compared to the conventional way of using 2D images. Material and methods: In this study, clinicians had to identify liver segments associated to lesions. Results: Twenty-eight clinicians with varying medical experience were recruited for the study. From a total of 150 lesions, 89 were correctly assigned without significant difference between the modalities. The median time for correct identification was 23.5 [4-138] s using the magnetic resonance imaging images and 6.00 [1-35] s using HoloLens (p < 0.001). Conclusions: The use of 3D liver models in mixed reality significantly decreases the time for tasks requiring a spatial understanding of the organ. This may significantly decrease operating time and improve use of resources.